PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Hermila Meiriana Putri (Universitas Slamet Riyadi, 2015)
The aim of this study are to analyze the effect of budgeting participation on job satisfaction, analyzing the effect of motivation on job satisfaction, and analyzing the influence of the participation of the preparation budgeting on job satisfaction moderated by motivation. This is a population with a sample research of accounting, finance, and administration with 40 employees of BPU Rosalia Indah as respondent. The technique of collecting data using questionnaires through validity and reliability test. Technique of data analyzing by classic assumption test, regression, hypothesis testing. The results of research show that (1) there is a significant positive effect of budgeting participation on job satisfaction of employees in the BPU Rosalia Indah. (2) There is a significant positive effect of motivation on employee’s satisfaction in the BPU Rosalia Indah. (3) There is no significant effect of budgeting participation on job satisfaction of employees in the BPU Rosalia Indah moderated by motivation. Keywords: budgeting participation, motivation, job satisfaction